Resolving Conflicts between Agriculture and the Natural Environment - Tanentzap, Andrew J.; Lamb, Anthony; Walker, Susan; Farmer, Andrew (PLOS Biology, 2015)
Agriculture dominates the planet. Yet it has many environmental costs that are unsustainable, especially as global food demand rises. Here, we evaluate ways in which different parts of the world are succeeding in their attempts to resolve conflict between agriculture and wild nature. We envision that coordinated global action in conserving land most sensitive to agricultural activities and policies that internalise the environmental costs of agriculture are needed to deliver a more sustainable future.